1999
DOI: 10.1002/(sici)1096-9861(19990125)403:4<459::aid-cne3>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric studies of the aged hippocampus: I. Volumetric analysis in behaviorally characterized rats

Abstract: The present investigation examined the structural integrity of the aged hippocampus by using computer-aided morphometry to quantify the volume of principal hippocampal circuits in young, mature adult, and aged Long-Evans rats. A key feature of the experimental design was that the status of hippocampal-dependent learning and memory was documented prior to histologic evaluation. The following regions, which were visualized by using Timm staining, were included in the analysis: 1) outer portions of the dentate gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
2
22
1
2
Order By: Relevance
“…In particular, Darbin et al (2004) found an age-related reduction in fast frequencies in EEG recordings and behavioral characteristics elicited during kainate treatment in aged Fischer 344 rats, suggestive of a change in seizure network activity. Alterations in seizure network activity could result from age-related alterations in synaptic connectivity (Barnes and McNaughton, 1980;Rapp et al, 1999;Smith et al, 2000), electronic coupling (Barnes et al, 1987), receptor and channel properties (Pitler and Landfield, 1990;Guti茅rrez et al, 1996), or the number and type of neurons (Shetty and Turner, 1998;Cadiacio et al, 2003;Stanley and Shetty, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Darbin et al (2004) found an age-related reduction in fast frequencies in EEG recordings and behavioral characteristics elicited during kainate treatment in aged Fischer 344 rats, suggestive of a change in seizure network activity. Alterations in seizure network activity could result from age-related alterations in synaptic connectivity (Barnes and McNaughton, 1980;Rapp et al, 1999;Smith et al, 2000), electronic coupling (Barnes et al, 1987), receptor and channel properties (Pitler and Landfield, 1990;Guti茅rrez et al, 1996), or the number and type of neurons (Shetty and Turner, 1998;Cadiacio et al, 2003;Stanley and Shetty, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, lesions restricted to the dorsal hippocampus or the CA1 cell field have been shown to disrupt spatial learning in rats (Davis et al, 1986;Moser et al, 1995). However, age-related spatial learning deficits in rats do not arise from hippocampal neuron loss (Rapp and Gallagher, 1996), implicating more subtle changes in synaptic structure or function (Rapp et al, 1999;Smith et al, 2000). In line with this thinking, impaired hippocampal synaptic plasticity, specifically long-term potentiation (LTP), has been prominently cast as a key factor in age-related cognitive decline (Foster, 1999).…”
mentioning
confidence: 99%
“…As was shown, these systems regulate in vivo the epileptiform activity and significantly influence the relapse severity, sensitivity, and prevalence [30,31]. Considerable modifications of synaptic connections, electrotonic coupling, features of receptors and channels, numbers and functions of specific-type neurons within neuronal networks develop due to aging [32][33][34][35][36][37]. Besides this, it was reported that age-dependent alterations also develop in the sodium/potassium equilibrium and extracellular volume, and these alterations noticeably affect neuronal synchronization and excitability [38][39][40][41].…”
Section: Discussionmentioning
confidence: 97%